A "Field" Under Construction: The State of Planning in Latin America and the Southern Turn in Planning: Introduction to the Special Issue on Latin America. Issue 1 (2nd January 2018) - Galland, Daniel; Elinbaum, Pablo
Abstract: This special issue takes a point of departure on the "southern turn in planning" with an emphasis on Latin America and seeks to contribute to the current wave of debates around international comparative planning. Its objective is to target the "state of the art" of planning interventions as well as contemporary forms of planning knowledge and academic scholarship across the region. In doing so, a number of key themes are identified through rationales ranging from the emergence of planning policies, practices and discourses to gaps between theory and practice, and then moving on to the state of planning education and the exchange of planning knowledge across different countries within the region. Based on these themes, the substance of the issue embraces inputs by academics with planning knowledge and expertise from Argentina, Mexico, Chile, Colombia, Uruguay, Brazil and Peru. The conclusion to the issue presents a cross-comparative analysis and synthesises a series of research axes aimed at designing a research agenda concerning planning in Latin America.